Technical feasibility of leadless left bundle branch area pacing for cardiac resynchronization: a case series. Issue 11 (24th September 2021) - Elliott, Mark K; Jacon, Peggy; Sidhu, Baldeep Singh; Smith, Lucy Jarrett; Mehta, Vishal S; Gould, Justin; Lee, Angela W C; Niederer, Steven; Defaye, Pascal; Rinaldi, Christopher A
Abstract: Background: Left bundle branch area pacing (LBBAP) is a novel form of conduction system pacing which can reverse left bundle branch block and deliver cardiac resynchronization therapy (CRT). The WiSE-CRT system delivers leadless endocardial pacing with symptomatic and left ventricular (LV) remodelling improvements following intervention. We report the technical feasibility of delivering leadless LBBAP using the WiSE-CRT system. Case summary: In Case 1, a 57-year-old male with ischaemic cardiomyopathy and complete heart block underwent implantation of the WiSE-CRT system, using a retrograde transaortic approach, after failed conventional CRT. Temporary left bundle stimulation from the LV septum achieved superior electrical resynchronization and equivalent haemodynamic response compared to endocardial pacing at the lateral LV wall. In Case 2, an 82-year-old gentleman with tachyarrhythmia-induced cardiomyopathy underwent WiSE-CRT implantation via a trans-septal inter-atrial approach, with the endocardial electrode successfully deployed in the LV septum. Discussion: Here we report the first case of deployment of the WiSE-CRT endocardial electrode in the LV septum and demonstrate the technical feasibility of leadless LBBAP. Entirely leadless CRT is an attractive option for patients with venous access issues or recurrent lead complications and has previously been successful using the WiSE-CRT system and a leadless pacemaker in the right ventricle. Further studies are required to assess long-term efficacy and safety of leadless LBBAP.